Mechanical stimulation enhanced estrogen receptor expression and callus formation in diaphyseal long bone fracture healing in ovariectomy-induced osteoporotic rats. Issue 10 (October 2016) - Chow, S.; Leung, K.; Qin, J.; Guo, A.; Sun, M.; Qin, L.; Cheung, W.
Abstract Summary Estrogen receptor (ER) in ovariectomy-induced osteoporotic fracture was reported to exhibit delayed expression. Mechanical stimulation enhanced ER-α expression in osteoporotic fracture callus at the tissue level. ER was also found to be required for the effectiveness of vibrational mechanical stimulation treatment in osteoporotic fracture healing. Introduction Estrogen receptor(ER) is involved in mechanical signal transduction in bone metabolism. Its expression was reported to be delayed in osteoporotic fracture healing. The purpose of this study was to investigate the roles played by ER during osteoporotic fracture healing enhanced with mechanical stimulation. Methods Ovariectomy-induced osteoporotic SD rats that received closed femoral fractures were divided into five groups, (i) SHAM, (ii) SHAM-VT, (iii) OVX, (iv) OVX-VT, and (v) OVX-VT-ICI, where VT stands for whole-body vibration treatment and ICI for ER antagonization by ICI 182, 780. Callus formation and gene expression were assessed at 2, 4, and 8 weeks postfracture. In vitro osteoblastic differentiation, mineralization, and ER-α expression were assessed. Results The delayed ER expression was found to be enhanced by vibration treatment. Callus formation enhancement was shown by callus morphometry and micro-CT analysis. Enhancement effects by vibration were partially abolished when ER was modulated by ICI 182, 780, in terms of callus formation capacity at 2–4 weeks and ER gene and protein expression at all time points. In vitro, ER expression in osteoblasts was not enhanced by VT treatment, but osteoblastic differentiation and mineralization were enhanced under estrogen-deprived condition. When osteoblastic cells were modulated by ICI 182, 780, enhancement effects of VT were eliminated. Conclusions Vibration was able to enhance ER expression in ovariectomy-induced osteoporotic fracture healing. ER was essential in mechanical signal transduction and enhancement in callus formation effects during osteoporotic fracture healing enhanced by vibration. The enhancement of ER-α expression by mechanical stimulation was not likely to be related to the increased expression in osteoblastic cells but rather to the systemic enhancement in recruitment of ER-expressing progenitor cells through increased blood flow and neo-angiogenesis. This finding might explain the observed difference in mechanical sensitivity of osteoporotic fracture to mechanical stimulation.